SUCCESSIVE OBTURATOR-OVERDENTURE DESIGNS FOR LONG HISTORY CLEFT PALATE PATIENT: RANCANGAN OVERDENTURE-OBTURATOR PADA PENDERITA CLEFT PALATE - Laith Mahmoud Abdulhadi (TALENTA, 2010)
A 39 year cleft palate lady had been treated since she was 19 years old by different design obturators after partial breakdown of surgical correction. The first obturator was fabricated into two pieces connected to each other using mini-dental magnets. A new obturator was prescribed to the patient and constructed in one piece with hollow opened box. Later, the box window was closed and retained by three ready-made ball stainless steel clasps. Two years later due to caries, a new obturator was designed with hollow palate and nasal box and retained by three magnets placed over three remaining abutment teeth into their cast copings.